Sistemas de comunicação quântica com óptica linear - Brito, Daniel Barbosa de (2007)
In this dissertation it is considered a quantum error correction system for coherent states of light and a complete optical system for probabilistic teleportation of single-photon polarization encoded qubit. Initially, the quantum error correction with the use of redundancy is analyzed. After that, it is presented a form of error correction using time-bin qubit without redundancies. Based on this last approach, a passive quantum error correction system, that is, without external control and synchronization, for quantum communication system employing coherent states, using only linear optical devices, is proposed. It is shown that the quantum error correction system also works for bipartite states of qubits. Following, the teleportation of quantum states is analyzed and an optical system for probabilistic teleportation of single-photon polarization encoded qubit, using only linear optical devices, is proposed. Finally, the error correction and teleportation topics are put together in the proposal of a probabilistic teleportation system using an error correction system for distribution of the entangled pair of photons